Effect of heat treatment on the structure, cavitation erosion and erosion–corrosion behavior of Fe-based amorphous coatings. (October 2015) - Zheng, Z.B.; Zheng, Y.G.; Sun, W.H.; Wang, J.Q.
Abstract: In this study, high-velocity oxygen-fuel sprayed amorphous coatings have been heat treated at various temperatures to form microstructures with crystalline phases. The structure, micro-hardness, cavitation erosion resistance and erosion–corrosion resistance of these coatings are compared. Crystalline phases are discovered in the coatings after heat treatments at 650 °C and 750 °C. The coating heat treated at 750 °C exhibits the poorest cavitation erosion resistance in 3.5 wt% NaCl solution among all coatings due to the degraded corrosion resistance. However, the hardness of the crystallized coating can reach 1000 Hv and the erosion–corrosion resistance of the heat treated coating is better than the untreated one. Highlights: The crystalline phases formed in the coatings at 650 °C and 750 °C were different. The hardness of the coating increased with increasing annealed temperature. Cavitation erosion resistance of coating annealed at 750 °C degraded in 3.5% NaCl. The erosion–corrosion resistance of coatings improved after heat treatments.